GAYA BAHASA IRONI DAN SARKASME KIKY SAPUTRI PADA TAYANGAN LAPOR PAK - Nurvia, Riska; Usman, Usman; Fitri, Sakinah (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2025)
This research aims to describe the linguistic style of Kiky Saputri irony and sarcasm in the show “Lapor Pak”; describe the meaning of Kiky Saputri's language style of irony and sarcasm in the show "Lapor Pak". This research uses qualitative research with qualitative descriptive methods. The research results showed that Kiky Saputri used 4 verbal irony data and 2 situational irony data in the "Lapor Pak" broadcast. Apart from that, there are 2 data of action sarcasm, 3 data of sarcasm as a result of action, 2 data of appeal sarcasm, and 2 data of epithet sarcasm. The meaning of the language styles of irony and sarcasm includes criticism, ridicule, satire, as well as conveying messages directly or indirectly, including criticism of someone's quote or statement. The conclusion of this research is that the dominant language style used by Kiky Saputri is the form of verbal irony and sarcasm resulting from actions. The use of irony and sarcasm is effective in criticizing social and political issues, and has a strong and memorable impact on the audience.